Shakespeare, Jonson, and the claims of the performative - Loxley, James, 1968- (Routledge studies in Renaissance literature and culture ;, 2013)
"This book will constitute an original intervention into longstanding but insistently relevant debates around the significance of notions of 'performativity' to the critical analysis of early modern drama. In particular, the book aims to:show how the investigation of performativity can enable readings of Shakespeare and Jonson that challenge the dominant methodological frameworks within which those plays have come to be read;demonstrate that the thought of performativity does not come to rest in the simplicity of method or instrumentality, and that it resists its own claim that language and action might be understood as unproblematically instrumental;demonstrate that this self-resistance occurs or takes place as a moment in the process of articulating the claims of the performative, and that this process is itself in an important sense dramatic"--